The Infidelity of Using Detective Story Formula in Enola Holmes Film Adaptation - Sabani, Irbatun; Istiani, Imas (Wanastra: Jurnal Bahasa dan Sastra, 2024)
Adapting a novel into a movie combines creative art and technical challenges. The film director is required to make the novel story that is lifted to the big screen have uniqueness from creative ideas with limited film duration, various creative interpretations, and commercial interests. The process will result in two-story forms: maintaining the novel's authenticity or changing specific components. Therefore, this research compares Nancy Springer's Enola Holmes novel, published in 2006, and Harry Bradbeer's film adaptation, released in 2020. This comparison is carried out to find the fidelity or infidelity of using the detective story formula in the Enola Holmes film related to the director's creativity and the technical challenges in the adaptation process. Using the descriptive qualitative method and Cawelti's detective story formula theory, the result of data analysis shows that Enola Holmes' novel is classified into the classic detective story formula. At the same time, the movie adaptation is categorized into the hard-boiled detective story formula. This theory is applied through the differences between the focus of the story, the setting, and the role of women. These differences lead to infidelity in using detective formulas that aim to develop and clarify the storyline and make some things more realistic when the novel's story is adapted into a movie that refers to commercial interests and audience satisfaction.